Capecitabine enhances sensitivity to oxaliplatin in advanced gastric cancer and the effects on patients’ FOXP1 and GGT levels - Xinyu Guo; Yi Liu (BMC Gastroenterology)
Abstract Objective To investigate the effect of capecitabine on the sensitivity of oxaliplatin and on the level of transcription factor forkhead box P1 (FOXP1) and gamma-glutamyl transpeptidase (GGT) in patients with intermediate and advanced gastric cancer. Methods A total of 152 Patients with advanced gastric cancer who were continuously diagnosed and treated in our hospital were selected as the study objects. The general data were retrospectively analyzed. The patients in the control group received oxaliplatin, while the patients in the study group received capecitabine on the basis of the control group. The FOXP1 expression level was detected using immunohistochemistry. Serum levels of GGT were measured by chemiluminescence. Protein levels were detected by Western blot. The prognostic factors were analyzed by the COX regression model. The Kaplan–Meier survival curve was used to analyze the survival of gastric cancer. Results The effective rates (complete response, partial response, and stability) of the study group and the control group were 94.74% and 76.32%, respectively. Compared with adjacent normal tissues, the expression level of FOXP1 in gastric cancer tissues was lower (P < 0.05). After treatment, the average expression level of FOXP1 in the gastric cancer tissue of the study group was higher than the control group (P < 0.05). Moreover, lower FOXP1 expression was associated with lower overall survival (OS) (1-year survival and 3-year survival were 75.76% and 53.03%, respectively) (P < 0.05). Further analysis showed that capecitabine combined with oxaliplatin down-regulated the expression of DNA repair related-proteins and up-regulated the expression of key molecules of the apoptosis pathway, thus enhancing the killing effect of oxaliplatin on gastric cancer cells (P < 0.05). Both the 1-year and 3-year survival rates of the study group were higher than that in the control group (P < 0.05). The 1-year survival rate of 152 patients with gastric cancer was 84.87% (129/152) and the 3-year survival rate was 63.17% (96/152). Age, tumor-node-metastasis (TNM) stage, lymph node metastasis, chemotherapy regimen, FOXP1, and GGT levels were important factors in determining OS. Conclusion Capecitabine effectively enhanced the sensitivity of intermediate and advanced gastric cancer to oxaliplatin, improved the therapeutic effect and ameliorated the prognosis of patients. Graphical Abstract